Clinical Evaluation of "Shock Bowel" Using Intestinal Fatty Acid Binding Protein. Issue 1 (January 2017) - Matsumoto, Shokei; Sekine, Kazuhiko; Funaoka, Hiroyuki; Funabiki, Tomohiro; Akashi, Taku; Hayashida, Kei; Shimizu, Masayuki; Orita, Tomohiko; Yamazaki, Motoyasu; Kitano, Mitsuhide
Abstract : ABSTRACT: "Shock bowel" is one of the computed tomographic (CT) signs of hypotension, yet its clinical implications remain poorly understood. We evaluated how shock bowel affects clinical outcomes and the extent of intestinal epithelial damage in trauma patients by measuring the level of intestinal fatty acid binding protein (I-FABP). We reviewed the initial CT scans, taken in the emergency room, of 92 patients with severe blunt torso trauma who were consecutively admitted during a 24-month period. The data collected included CT signs of hypotension, I-FABP, feeding intolerance, and other clinical outcomes. Demographic and clinical outcomes were compared in patients with and without hemodynamic shock and shock bowel. Shock bowel was found in 16 patients (17.4%); of them 7 patients (43.8%) did not have hemodynamic shock. Certain CT signs of hypotension, namely free peritoneal fluid, contrast extravasation, small-caliber aorta, and shock bowel, were significantly more common in patients with hemodynamic shock than in patients without ( P  < 0.05). Injury severity score and the rate of consciousness disturbance were significantly higher in patients with shock bowel than in patients without ( P  < 0.05). The rate of feeding intolerance and median plasma I-FABP levels were significantly higher in patients with shock bowel than in patients without (75.0% vs. 22.4%, P  < 0.001 and 17.0 ng/mL vs. 3.7 ng/mL, P  < 0.001, respectively). There was no difference in mortality. In conclusion, shock bowel is not always due to hemodynamic shock. It does, however, indicate severe intestinal mucosal damages and may predict feeding intolerance.